CLINICAL CHARACTERISTICS AND ONE-YEAR TREATMENT OUTCOMES IN A COHORT OF PATIENTS WITH FAMILIAL HYPERCHOLESTEROLEMIA IN SINGAPORE: FHCARE REGISTRY - Pek, Sharon; Hoe, Jeremy; Dissanayake, Sanjaya; Zulkifli, Atiqa Binte; Selvakumar, Madhuumetaa D/O; Jin, Terrance Chua Siang; Shyong, Tai E; Siang, Eric Lim Tien; Drum, Chester; Nastar, Fathima Ashna; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Familial hypercholesterolemia (FH) is an autosomal dominant condition characterized by high low-density lipoprotein cholesterol (LDL-C), increasing the risk for premature cardiovascular disease (CVD). The gold standard for diagnosis is the identification of the pathogenic mutation (LDLR, APOB and PCSK9). We aim to compare clinical characteristics and treatment outcomes in patients with different FH-causing variants. METHODOLOGY Patients with possible and definite FH using the Simon-Broome criteria were recruited from acute hospitals and specialist centers in Singapore. Biochemical indices including total cholesterol (TC) and LDL-C were measured in CAP-accredited clinical laboratories. Genetic analysis of peripheral blood cells was performed in the same research laboratory using next-generation sequencing on lipid-related genes, including LDLR, APOB and PCSK9. CVD was defined as myocardial infarction, ischemic stroke and peripheral arterial disease. RESULTS From June 2015 to July 2023, 965 probands were recruited. The median age at entry was 39.7 years (range 29.6 to 53.4), BMI of 25.2 ± 4.68 kg/m2 with a predominance of males (65%). In those with heterozygous FH, pathogenic and likely pathogenic variants were predominantly LDLR (n = 207), followed by APOB (n = 22) and PCSK9 (n = 2). Comparing heterozygous LDLR versus no variants and APOB variants, those with LDLR variants were significantly younger, had significantly higher TC and LDL-C levels (mmol/l): (8.43 ± 1.89) and (6.70 ± 1.87) versus (7.47 ± 1.53) and (5.65 ± 1.21) vs (7.05 ± 1.41) and (5.45 ± 1.28), p <0.0001, higher prevalence of xanthomas, n = 55(23.0%) vs 50(7.5%) and 2 (9.1%), p <0.0001, lower prevalence of hypertension 21(8.8%), 115(18.2%), p = 0.036. (17.2%) and lower prevalence of type 2 diabetes: 14(6.0%) vs 75(11.2%) and 2(9.1%), p = 0.038. There were no statistical differences in the prevalence of CVD and corneal arcus. At recruitment, a significantly higher proportion of those with LDLR variants vs no variants and APOB variants were on high-intensity statins: 94 (41.2%), 149 (23.4%) and 4 (20.0%), p = 0.001, a significantly higher proportion of patients with LDLR and APOB variants were on ezetimibe: 74 (37.0%), 5(31.3%) vs 91(16.3%), p <0.0001 After treatment for 12 months. Those with LDLR variants vs no variant vs APOB variants: TC (mmol/l): (5.34 ± 1.82) vs (5.40 ± 1.79) and (5.13 ± 1.09), p = 0.457. LDL-C: (3.64 ± 1.65) vs (3.47 ± 1.53) and (3.45 ± 1.00), p = 0.067. In those with LDLR variant vs no variants and APOB variants: 39(57.4%) were on high-intensity statins, p = 0.270. Those with LDLR variants vs no variant vs APOB variants: Those who achieved 50% LDL-lowering from baseline and target LDL-C<1.8 mmol/l: 15(5.3%), vs 53(8.0%) vs 1(4.8%), p = 0.705. CONCLUSION Our data showed that, despite being younger, patients with LDLR variants had significantly higher TC and LDL-C levels at baseline, lower prevalence of diabetes and hypertension, and similar prevalence of CVD. While TC and LDL-C levels were significantly lower in all groups after 12 months, not all patients were on high-intensity statins. Probands attaining LDL-C goals were low, suggesting undertreatment. Increased awareness for treatment in these patients should be emphasized.